Palm oil thorn induced tumour-like lesion: a review of 4 cases - Awang, Mohd Shukrimi; Che Ahmad, Aminudin; Zakaria, Zamzuri; Zulkifly, Ahmad Hafiz; Ab Rahman, Jamalludin (2007)
It is not widely recognized that palm oil thorn injuries can produce progressive and persistent reaction in the bone joint and surrounding tissue. The natural history is unique and most of the investigations are inconclusive. We reviewed four cases of tumor like lesion: two cases were around the elbows and two cases at the foot, which developed following injuries caused by palm oil thorns. The typical presentation is transient acute synovitis followed by a relatively asymptomatic period. It can also manifest later with chronic or recurrent inflammation mimicking septic arthritis, osteomyelitis or bone tumor often after the thorn injury was forgotten. The hand is the most commonly affected. Lesions of the elbows and foot are very rare. The tissue for culture and histopathologically examination together with administration of broad spectrum antibiotics are needed for the treatment although they are negative and inconclusive. The definite treatment includes operative debridement and removal of thorn particles, even though in most cases the particles cannot be found either due to irrigation or because they are too small to be seen.